Contrast-enhanced ultrasound does not discriminate between community acquired pneumonia and lung cancer. Issue 2 (14th October 2016) - Sperandeo, Marco; Rea, Gaetano; Grimaldi, Maria Arcangela; Trovato, Francesca; Dimitri, Lucia M C; Carnevale, Vincenzo
Abstract : We investigated if contrast-enhanced ultrasound (CEUS) may differentiate community acquired pneumonia (CAP) from lung cancer (LC). Among 1374 patients admitted in a 5-year period for lung opacities, 728 (329 CAP and 399 LC) were investigated by CEUS, comparing the time of appearance, disappearance, duration and pattern of distribution of contrast enhancement (CE). The patients with CAP and LC did not differ in terms of age, time of CE appearance, disappearance and duration or CE distribution. Our data show that the timing and pattern of CE detected by chest CEUS does not distinguish between CAP and LC and overly optimistic beliefs on this matter should be abandoned.